Superior Labor Able to Improve the Quality of Traditional Herbs in the Special Region of Yogyakarta (DIY) - Komalasari, Dewi Tri; Sihombing , Unedo Hence Markus; Ekawaty , Donna (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2025)
Formely known as birth defects, congenital anomalies are structural or functional abnormalities present at birth that can lead to physical disability, developmental problems or other health issues. Congenital abnormalities can affect organ shape, organ function or both. Past researchers have found that there are many congenital abnormalities of infants and some of them cause lifelong disability to the infant. If not prevented and treated quickly, they can be a major problem causing infant mortality during their first year of life. One way to prevent congenital abnormalities in babies is to provide healthy and nutritious food and traditional herbs during the mother's pregnancy. Traditional herbs have many benefits, such as body immunity, disease treatment, and maintaining the health of the baby while in the mother's womb. One of the best producers of traditional herbs in Indonesia is the Special Region of Yogyakarta (DIY), which has the highest tourism economy on the island of Java. A high economy is inseparable from the excellence of the existing workforce. A superior workforce will be able to produce products that can be useful for the community, especially pregnant women. The method used in this research is a structured interview method followed by the results of a site survey of nine respondents consisting of traditional herb lovers in a pregnant condition and traditional herb sellers. The results of this study show that a superior workforce can improve the existing tourism economy with the products produced, especially in traditional herbs in the Special Region of Yogyakarta (DIY)